2021
DOI: 10.1155/2021/1544208
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Tracer Positron-Emission Tomography Using Prostate-Specific Membrane Antigen and Fluorodeoxyglucose for Staging of Prostate Cancer: A Systematic Review

Abstract: PSMA PET is more accurate than conventional imaging (CT/bone scan) for staging of intermediate- or high-risk prostate cancer (PCa), but 5–10% of primary tumours have low PSMA ligand uptake. FDG PET has been used to further define disease extent in end-stage castrate-resistant PCa and may be beneficial earlier in the disease course for more accurate staging. The objective of this study was to review the available evidence for patients undergoing both FDG and PSMA PET for PCa staging at initial diagnosis and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…Unfortunately, the rapid progression of Pca resulted in the patient's death within 2 months. Studies in literature have reported that FDG positivity in Pca is associated with poor prognosis, as seen in our example 1,2 . Also, preliminary studies showed that fibroblast activation protein is expressed from cancer-related fibroblasts in the tumor microenvironment as well as from the metastases of Pca 3,4 .…”
mentioning
confidence: 51%
“…Unfortunately, the rapid progression of Pca resulted in the patient's death within 2 months. Studies in literature have reported that FDG positivity in Pca is associated with poor prognosis, as seen in our example 1,2 . Also, preliminary studies showed that fibroblast activation protein is expressed from cancer-related fibroblasts in the tumor microenvironment as well as from the metastases of Pca 3,4 .…”
mentioning
confidence: 51%
“…Lower PSMA expression has been previously reported in treatment-refractory prostate cancer patients. [49][50][51][52][53][54] In response to androgen-deprivation therapy, CRPC tumors can progress towards a neuroendocrine phenotype and lose PSMA expression. Herein, we provide blood-based evidence that both PSMA + and STEAP1 + -EVs can be promising for identification of aggressive prostate cancer including those characterized by neuroendocrine features and low serum PSA levels.…”
Section: Discussionmentioning
confidence: 99%
“…However, fluoride PET/CT had a significantly higher detection rate for bone metastases and could be a relevant complement to PSMA PET in certain scenarios. PSMA-expression might be reduced or absent in dedifferentiated PCa and a discrepancy between PSA levels and PSMA PET findings should potentially trigger additional imaging with higher sensitivity in biochemical relapses after treatments with curative intent (McGeorge et al 2021 ). PSMA PET/CT followed by fluoride PET/CE-CT might also be a relevant combination for ruling out PSMA-negative lesions before treatment with PSMA-targeted radionuclide therapies.…”
Section: Discussionmentioning
confidence: 99%